The Effect of Education and Job Training on Increasing Employee Productivity at PT. Sagami Indonesia - Resi Amalia; Risa Kartika Lubis (Junal Ilmu Manajemen, 2021)
The purpose of this study was to determine and analyze the effect of education and job training on increasing employee productivity, either partially or simultaneously. The approach used in this research is an associative approach. The population in this study were all employees at PT. Sagami Indonesia. The sample in this study using the Slovin formula totaling 92 employees of PT. Sagami Indonesia. Data collection techniques in this study used interview techniques, documentation study, observation, and questionnaires. The data analysis technique in this study used the Multiple Liner Regression Analysis Test, Hypothesis Test (t test and F test), and the Coefficient of Determination. Data processing in this study used the SPSS (Statistical Package for the Social Sciens) software program version 24.00. The results of this study prove that partially and simultaneously education and job training have an effect on increasing the work productivity of employees at PT. Sagami Indonesia